BER Performance based on Orthogonal Frequency Division Multiplexing in Underwater Acoustic Communication System on non-Gaussian Distribution - Ahmed, Mustafa Sami; Jawhar, Yasir Amer; Ghanim, Mustafa (Engineering, Technology & Applied Science Research, 2025)
The field of underwater communication has attracted significant attention from researchers interested in investigating activities below the water's surface. The underwater environment presents unique challenges such as limited bandwidth, low data rates, propagation delays, and a high Bit Error Rate (BER). This study focuses on Underwater Acoustic (UWA) communication and analyzes error performance in Amiriyat Fallujah, Al Anbar, Iraq. Orthogonal Frequency Division Multiplexing (OFDM) is a multiplexing technique that has been adopted in UWA along with turbo and convolutional codes. The research revealed that the noise in UWA does not follow a Gaussian distribution, whereas the t-distribution noise is fitted to the collected data. Furthermore, the turbo code exhibited superior performance compared to the convolutional code, achieving a 4.5 dB advantage at a BER of 10-3.